The Effects of Social Capital on Chinese Consumers' Online Impulse Buying in Social Commerce Environment (Global Journal of Human-Social Science, 2021)
The purpose of this study is to examine the impact of social capital including social interaction, shared language and trust on Chinese consumer online impulse buying in social commerce platforms. To verify the hypothesis, we surveyed the Chinese customers who have buying experiences of using social commerce by snowball sampling technique. After analyzing 548 valid data, we confirmed that three dimensions of social capital, social interaction, shared language and trust, positively affects both peer intrinsic motivation and peer extrinsic motivation. In addition, peer motivation exerts a positively impact on consumer impulse purchases on social commerce. The findings not only provide a new theoretical perspective for studying consumers' impulse buying behavior in theory, but also have important implications for the online sellers in their follower's groups to improve online marketing.
Keywords: consumer socialization theory; online impulse buying; peer motivation; social capital; social commerce